2011
DOI: 10.1089/cyber.2010.0135
|View full text |Cite
|
Sign up to set email alerts
|

The Wired Generation: Academic and Social Outcomes of Electronic Media Use Among University Students

Abstract: Little is known about the influence of electronic media use on the academic and social lives of university students. Using time-diary and survey data, we explore the use of various types of electronic media among firstyear students. Time-diary results suggest that the majority of students use electronic media to multitask. Robust regression results indicate a negative relationship between the use of various types of electronic media and firstsemester grades. In addition, we find a positive association between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
298
4
12

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 496 publications
(334 citation statements)
references
References 34 publications
20
298
4
12
Order By: Relevance
“…24 A growing body of evidence suggests that the use of media while engaged in academic tasks has negative consequences on learning. 25,26 …”
Section: Risks Of Mediamentioning
confidence: 99%
“…24 A growing body of evidence suggests that the use of media while engaged in academic tasks has negative consequences on learning. 25,26 …”
Section: Risks Of Mediamentioning
confidence: 99%
“…However, other research partially contradicts these conclusions. For example, a study of undergraduate electronic media use (including time spent on social networking sites, email, chat/IM, cell phone communication or text messaging, video or online games, TV or movie viewing) by Jacobsen and Forste (2011) revealed that online communication facilitated rather than replaced face-to-face social interaction. However, this study did find negative academic consequences (a negative association between electronic use and GPA), paralleling the previous research.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers, for example, in a cross-sectional study among a sample of undergraduate private college students in the United States (US), found high videogame use to be associated with low grade point average (GPA) (Weaver, Kim, Metzer, & Szendrey, 2013). Associations between calling and texting, and low self-reported GPA and a self-reported measure of academic difficulty were also found among a sample of first year university students from the US and a sample of Taiwanese female university students, respectively (Hong, Chiu, & Huang, 2012;Jacobsen & Forste, 2011). Similarly, in a more recent study done on undergraduate college students from a public US university, a negative association between texting and academic performance was found (Lepp, Barkley, & Karpinski, 2014).…”
mentioning
confidence: 63%